Material didáctico basado en el constructivismo para mejorar el aprendizaje de los polígonos del bloque geométrico, en los estudiantes de octavo grado paralelo A, de educación general básica de la unidad educativa anexa a la UNL, de la ciudad de Loja, periodo 2013-2014 - Huiracocha Huiracocha, Marco Vicente (2015)
The research was aimed EDUCATIONAL MATERIAL BASED CONSTRUCTIVISM LEARNING TO IMPROVE THE ESTATES OF GEOMETRIC BLOCK IN EIGHTH GRADE STUDENTS OF PARALLEL, BASIC EDUCATION GENERAL EDUCATION UNIT ATTACHED TO UNL, CITY Loja, PERIOD2013-2014. The objective of the research process was proposed as follows Use teaching materials based on constructivism learning allows polygons. The research answered a descriptive design (diagnosis) and quasi- experimental. The methods used in your order were: Comprehensive, diagnostic, models, application, assessment of the effectiveness of educational materials for teaching polygons. The main finding demonstrated in this research is that cognitive deficiencies or difficulties in learning needs of polygons can be reduced or mitigated through the implementation of educational material based on constructivism.